Peran Satuan Polisi Pamong Praja dalam Penertiban Masyarakat Terhadap Waktu Buang Sampah di Kota Palangka Raya - Ronald Hadibowo Sangalang; Valentino Tabang; Yunus Praja Panjika; Firman, Firman; Asep Ikbal (FKIP, Universitas Palangka Raya, 2025)
Effective waste management requires active community participation and consistent enforcement of regulations. In Palangka Raya City, a time-restricted waste disposal policy has been implemented, as stipulated in the Mayor Regulation (Perwali) of Palangka Raya No. 43 of 2017 concerning the Implementation of Regional Regulation No. 1 of 2017 on Waste Management and Environmental Cleanliness. However, violations of this regulation still frequently occur. This study aims to analyze the role of the Civil Service Police Unit (Satpol PP) of Palangka Raya City in enforcing compliance with designated waste disposal times. Using a descriptive qualitative approach, data were collected through interviews, field observations, and document analysis. The findings reveal that although Satpol PP has carried out its educational, preventive, and repressive functions, low public awareness remains the primary obstacle to effective enforcement. Most offenders claimed to be unaware of the regulation, indicating a lack of intensive socialization and weak dissemination of information. Therefore, stronger cross-sector collaboration and more persuasive and participatory approaches are needed to foster a culture of environmental discipline within the community